Measuring Physical Garment Durability: An assessment of 47 T-shirts - Morris, Kate Elizabeth; Joynes, Amanda; Summer, Mark; Scott, Eleanor; Taylor, Mark (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Designing for durability, both physical and emotional, has been identified as non-negotiable in the battle against overconsumption, underutilization and the devasting effects of climate change. There is currently no consistent method of measuring physical garment durability or the ability to compare garments on the market. This study presents a reproducible and novel method for measuring and ranking the physical durability of 47 t-shirts. Multiple durability factors were used to modulate the ranking whereas previous studies have only reported on single factors to evaluate durability. The benchmarking results reveal that price cannot be used as an indicator of durability and that fabric composition does influence the physical durability of a t-shirt. The garments in this study were donated by the signatories of the Waste Resource Action Programme’s (WRAP) Textile 2030 initiative as part of their strategy to reduce the environmental impact of UK fashion.